Ecological Compensation and Comprehensive Zoning of Cultivated Land Based on Ecosystem Service Value and Extended Three-Dimensional Ecological Footprint Model: A Case Study of Shandong Province - Jia Xiang; Junjun Niu (Land)
At present, with the rapid development of urbanization and industrialization, the contradiction between development and cultivated land protection is exacerbated. Scientifically quantifying ecosystem service value and constructing an ecological compensation mechanism of cultivated land are significant paths for cultivated land protection. This study originates from an extended three-dimensional ecological footprint model, introduces a carbon footprint accounting path, and thoroughly evaluates the sustainable use of farmland ecology. It aimed to accurately calculate the ecosystem service value of farmland, formulate ecological compensation standards, establish an ecological compensation model to measure the total amount of ecological compensation for cultivated land, and delineate the “five-zone map” of ecological compensation for farmland. (1) There is a partial spatial heterotopia phenomenon between ecological consumption and ecological services. (2) In 2022, the ecosystem service value of cultivated land in Shandong Province is high, reaching CNY 78.479 billion. Overall, exported the ecological service value of cultivated land to the outside world. Qingdao, Yantai, and Weihai are farmland ecological compensation zones, with a compensation amount of CNY 71 million. (3) The priority compensation zones are Qingdao and Yantai on the Shandong Peninsula. The priority compensated zones are mainly located in the northern region of Shandong. Exploring ecological compensation for cultivated land ecology at the spatial and temporal scale has important value for ecological protection and security of cultivated land.